The role of religion on stress and social skills of university students in multi-religious border environments - Sánchez-Bolívar, Lionel; Vázquez, Lindsay Michelle; Escalante-González, Sergio; Rodríguez-Sabiote, Clemente; Contreras-Rodríguez, María José (Psychology, Society & Education, 2025)
When it comes to constructing the professional profile of university students, it is essential to consider the competencies and skills necessary for their personal and social development. In this regard, both social skills and the way in which students experience and cope with stress will be paramount. These variables will be influenced by the impact of religions in environments where several converge, in turn, shape the profile of the student population. The analysis of this interaction will contribute to refining the teaching-learning process. The aim of this study, employing a quantitative, descriptive, exploratory, and correlational design, is to examine the relationship between religion and the social skills and stress levels of university students in cross-border and multi-religious environments in Ceuta and Melilla. For this endeavor, a sample of 436 students (78.9% women; Mage = 22.5, SD = 5.26) was selected, and they were administered a questionnaire comprising two scales: the Social Skills Scale and the Perceived Stress Scale. The main results indicate that religion is related to social skills, with Muslim students exhibiting higher levels of social skills in expressing feelings and anger, while students of religions with mid-lower presence present higher levels in interrupting social interactions and expressing denial. This study demonstrates the need to establish training program for these skills as a bridge of connection between religions.